Clinical Management Strategies and Implications for Parenteral Nutrition Drug Shortages in Adult Patients. Issue 1 (8th November 2013) - Hassig, Tanna B.; McKinzie, Brian P.; Fortier, Christopher R.; Taber, David
<x xml:space="preserve">Abstract</x> Drug shortages affect every aspect of patient care, including and especially, nutrition therapy. The purpose of this review is to discuss current parenteral nutrition–related drug shortages, including causes and duration of the disruptions, and provide recommendations for managing specific nutritional shortages that minimize negative patient care outcomes. A general framework for the management of current and future shortages is presented.